P06.07 Germline mutation of SMARCE1 gene in a family with spinal meningiomas. (9th September 2021) - Giunti, L; Rinaldi, B; Serio, V; Buccoliero, A; Fiorentini, E; Casati, G; Iorio, A; Marturano, A; Genitori, L; Sardi, I
Abstract: BACKGROUND: Meningioma is the most common benign primary intracranial tumor, arising from arachnoid cells of the meninges, but in 20% of cases displays aggressive behavior. Meningiomas are mainly sporadic and the familial forms are very rare. Meningioma account for a small subset (1–4%) of all pediatric brain tumors and may be associated with hereditary tumor predisposition syndrome caused by germline mutations of NF2, SMARCB1, SUFU, and SMARCE1 genes. MATERIAL AND METHODS: We present a case of a 16-year-old girl with spinal clear cell meningiomas (CCMs) WHO II with a second spinal lesion identified during the follow-up. Considering the multiple lesions, we performed Whole Exome Sequencing (WES) on DNA from peripheral blood to search for an underlying CCMs tumor predisposition syndrome (#607174). RESULTS: We identified a heterozygous frameshift variant c.439delA (p.Ser147fs) in SMARCE1, chromatin remodelling factor that acts as a tumor suppressor gene. Meningioma analysis by Sanger sequencing showed a loss of heterozygosity (LOH) of the wild-type allele. We identified the c.439delA in the constitutional DNA of the father and the sister but not in the mother. At the moment, the father is asymptomatic and the 14 years old sister showed two spinal lesions (meningiomas likely) at the first MRI. CONCLUSION: We report a family study of hereditary tumor predisposition syndrome to CCMs with SMARCE1 mutation in which are present two asymptomatic carriers with different ages and gender. The asymptomatic carriers will undergo neurological examination and MRI of the brain and spine, according to a screening protocol. The incomplete penetrance phenomenon is known in SMARCE1-related families with CCMs and it is probably due to the interaction of SMARCE1 with yet unidentified genes.